Bloch Oscillations of Hybrid Light-Matter Particles in a Waveguide Array - Beierlein, Johannes; Egorov, O. A.; Harder, T. H.; Gagel, P.; Emmerling, M.; Schneider, C.; Hoefling, S.; Peschel, Ulf; Klembt, Sebastian (Advanced Optical Materials, 2021)
Bloch oscillations are a phenomenon well known from quantum mechanics where electrons in a lattice experience an oscillatory motion in the presence of an electric field gradient. Here, the authors report on Bloch oscillations of hybrid light−matter particles, called exciton-polaritons (polaritons), being confined in an array of coupled microcavity waveguides. To this end, the waveguide widths and their mutual couplings are carefully designed such that a constant energy gradient is induced perpendicular to the direction of motion of the propagating polaritons. This technique allows us to directly observe and study Bloch oscillations in real- and momentum-space. Furthermore, the experimental findings are supported by numerical simulations based on a modified Gross–Pitaevskii approach. This work provides an important transfer of basic concepts of quantum mechanics to integrated solid state devices, using quantum fluids of light.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Bloch oscillations; exciton-polaritons; polariton condensation; waveguides